Pengaruh Kualitas Layanan Akademik terhadap Kepuasan Mahasiswa di Lembaga Pendidikan Smart Fast Global Education Pekanbaru - Andriani, Dessy; Seri Ramadanni (Bedelau: Journal of Education and Learning, 2021)
The purpose of this study was to determine the influence of service quality delivery of goods on customer satisfaction in PT. Inti Duta Logistik Pekanbaru. The sample in this study were customer in PT. Inti Duta Logistik Pekanbaru totaling 90 people. While the variables examined in this study is the service quality and customer satisfaction. Analysis of data using simple linear regression method using validity, reliability, R2 and t test. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). Based on the results obtained that the service quality simultaneously affect the customer satisfaction with a value of correlation R = 0.521 which shows the close relationship between the service quality and customer satisfaction in PT. Inti Duta Logistik Pekanbaru. While the R-square at 0.403 which can mean service quality has a contribution of 40.3% contribution to customer satisfaction in PT. Inti Duta Logistik Pekanbaru. Partially obtained service quality positive and significant effect on customer satisfaction in PT. Inti Duta Logistik Pekanbaru with signifivantly 0.002 smaller than alpha 0.05. With simple linear regression equation in this study : Y = 6.489 + 0.113X.